Chyloid Fat Carried Adipose-Derived Mesenchymal Stem Cells Accelerate Wound Healing Via Promoting Angiogenesis. Issue 4 (October 2021) - Geng, Yinan; Yang, Jinxiu; Li, Shiyi; Chen, Minliang
Abstract : Abstract: Impaired wound healing is responsible for significant morbidity and mortality worldwide. It is necessary to find a stable, efficient, and safe method to promote soft tissue wound healing. Fat grafting has become increasingly popular in contouring procedures. However, more recently, there has been an emphasis on its regenerative potential. In this study, we established the wound healing model using nude mice. Hematoxylin and eosin and Masson stainings were performed to assess the effect of chyloid fat on the histology of wound healing. A laser Doppler perfusion imager was used to evaluate the blood perfusion of wounds. Immunohistochemistry was carried out to detect the expression of CD31 in wound tissues. The results suggested that after treatment with granule fat or chyloid fat, wound healing was accelerated and blood perfusion was promoted. In addition, granule fat or chyloid fat treatment promoted the angiogenesis of the wound. In addition, we evaluated the amount of adipose-derived mesenchymal stem cells in chyloid fat and granule fat. It was found that chyloid fat contained more adipose-derived mesenchymal stem cells than granule fat did. In conclusion, we proved that chyloid fat could significantly accelerate the wound healing process via promoting angiogenesis. The adipose-derived mesenchymal stem cell plays a critical role in this effect of chyloid fat.